(untitled) (International Journal of Environmental Sciences, 2025)
This study introduces a novel and efficient approach for solving Fully Fuzzy Linear Programming Problems (FFLPP) by leveraging Triangular Fuzzy Numbers (TFN). The proposed method simplifies FFLPP by converting it into an equivalent Crisp Linear Programming Problem (LPP) through a systematic defuzzification process. This transformation ensures computational efficiency while maintaining solution accuracy. Comparative evaluations against existing techniques highlight the advantages of the proposed methodology. Numerical examples are included to validate the approach and demonstrate its effectiveness in practical applications.